Katalog ‘Elite’ Kitab Asia Tenggara - Muhammad Nida' Fadlan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2026)
Midori, Kawashima, et.al (eds.). 2025. Catalogue of Southeast Asian Kitabs of Sophia University: Third and Expanded Edition. Tokyo: Institute of Islamic Area Studies, Sophia University. Abstract: The new edition of the Catalogue of Southeast Asian Kitabs of Sophia University marks a massive decolonizing of archives. Its extensive and structured scale makes it an essential reference for scholars mapping the intellectual traditions of Islam in Southeast Asia. This review, however, reveals the catalogue’s ‘elitist’ nature, as it systematically marginalizes the tradition of textual reproduction at the grassroots level, which is an essential locus for the everyday transmission of Islamic knowledge. This limitation is supported by the absence of historically significant transregional print corpora, a gap that demonstrates inconsistency even within its prioritized domains. This article argues that precisely within these limitations, the catalogue makes an unexpected contribution. It functions as a definitive map of the “homework” awaiting future researchers, while radically affirming that the true richness of the Southeast Asian kitab tradition is far more extensive and dynamic than what can be represented by this catalogue.